Study on factors of fake news spreading on the halal status of food products in Malaysia / Shofiyyah Moidin … [et al.] - Moidin, Shofiyyah; Ismail, Nur Auni Syafiqah; Mohd Ashmir Wong, Muhammad Syukri; Harun, Nur Hafizah; Mamat, Norazlina (Academy of Contemporary Islamic Studies (ACIS), 2021)
Fake news spreading issues in Malaysia are getting serious and worse and not to be forgotten it also happens toward halal food products. Fake news information about halal food products is usually spread on social platforms like Facebook, Twitter, WhatsApp etc due to easy sharing features and it is constantly updated. Hence, this study aims to identify the factors of fake news spreading on the halal status of food products in Malaysia. The study employed a qualitative method using semi-structured interviews involving two (2) informants from the Section of Communication and Corporate, JAKIM. The gathered data were analysed via thematic analysis using NVivo 10 to classify it into nodes. Findings from this study found that the factors of fake news dissemination on halal food products in Malaysia occur due to haste attitude, racial and religious sentiment, attention seeker behavior, fierce business competition, lack of halal awareness, easily influenced as well as no access to get information or news. Hence this study is able to highlight the issue of fake news spreading in the halal food industry.